Bondswomen's Work on the Cotton Frontier: Wagram Plantation, Arkansas - Jones, Kelly Houston (Agricultural history, 2015)
This essay attends to the work life of women on a plantation called Wagram, located on the Arkansas cotton frontier. Through an examination of this absentee-owned farm in one rugged corner of the Old Southwest, it uncovers women who faced challenges that differed from those faced on the classic cotton plantation. This was most obvious in the role of women as prime workers of the crop, but includes gender politics that omitted the white planter family, and the meaning of space.